Professional Competence of Islamic Religious Education Teachers in Improving Student Learning Achievement: A Case Study at Madrasah Aliyah Negeri 2 Ponorogo - Nastiti, Sekar Arum; Supriyatno, Triyo; Muslimin, Imam (AS-SABIQUN, 2025)
Teacher competency plays a critical role in shaping student learning outcomes, particularly in the context of religious education. This study explores the professional competence of Islamic Religious Education (IRE) teachers at MAN 2 Ponorogo and examines how their professional skills contribute to improving student achievement. The research also investigates the challenges faced by IRE teachers, the strategies they employ to address these challenges, and the impact of their competence across cognitive, affective, and psychomotor domains of student learning. Using a qualitative descriptive approach, data were collected through classroom observations, interviews, and document analysis. The findings demonstrate that IRE teachers at MAN 2 Ponorogo meet the five key indicators of professional competence, including mastery of subject matter, pedagogical planning, instructional implementation, assessment ability, and reflective practice. However, teachers encounter several challenges, such as low student interest in religious education, managing diverse student backgrounds, and the intrusion of personal issues into the instructional process. Despite these obstacles, the professional competence of IRE teachers positively influences student learning by fostering a holistic educational experience that integrates intellectual, emotional, and behavioral development. These findings underscore the significance of sustained professional development for IRE teachers and provide valuable insights for enhancing the quality of religious education in secondary schools.